EFEK AROMA EKSTRAK MELATI TERHADAP PENGURANGAN NYERI PERSALINAN KALA I FASE AKTIF PADA PARTURIENT - Oktavia, Nike Sari (Jurnal Ipteks Terapan, 2017)
Labor pain arising from physical and psychological reflex response of from the pain that experienced by the patient. Jasmine essential oil is proven to nervous exhoustion, reduce pain, emotional distress, reduce anxiety, energy, and euphoria that everything that is needed by a mother while facing the birth process. Purpose of this study was to determine whether the jasmine essnstial oil can be used to reduce the pain of the active phase on first stage of parturient. This study used a quasi-experimental method, the sampel was 48 people inpartu who are in the active phase of the first stage of labor. Study subjects were devided into 2 groups; jasmine essential oil (n = 24) and control (n = 24). Pain assessed twice in each group with a numerical rating scale (NRS), that when the woman is in the active phase before inhalation the smell of jasmine essential oil and at the end of the first stage after inhalation the smell. Test statistical analysis using Wilcoxon Signed Ranks test and Mann Whitney test.  The result is; in jasmine essential oil group the median 6 with a range  4-9 decreased to 4 (3-9), while controls had increased pain intensity with a median value of 4.5 (2-10) to 9 (4 -10). There are difference between pain assesment I and II in both groups p = 0.000 (p <0,05). Comparison between jasmine essential oil  group and control group p = 0.000 (p <0,05).      Keyword: Jasmine essential oil, labor pain